The Boundaries of Divine Ontology: The Inclusion and Exclusion of Meṭaṭron in the Godhead - Abrams, Daniel (Harvard theological review, 1994)
One of the central aspects of Jewish theology, and Jewish mysticism in particular, is the conception of the nature of God's being and the appearance of the divine before humanity. No one view has dominated the spectrum of Jewish interpretations, since the biblical text is the only common frame for the wide variety of speculations. At issue is whether the one God depicted in the Hebrew Bible is manifest to humans directly or through the agency of a divine, semidivine, or created power. Even the nature of angelic figures in the Bible remains a matter of debate, both in its original context and through later interpretations. Does the angelic figure physically represent God's form, or is it a literary device that metaphorically describes God's presence? The same is true of divine anthropomorphism in the Bible. Do the descriptions of God's hands or feet imply that God possesses a definite shape similar to that of human bodies, or should these descriptions also be viewed metaphorically, reinforcing a similar view to that expressed about angelic figures: no physical characteristics can be attributed to anything heavenly or divine? Finally, how does this accord with the spatial manifestation of God in the tabernacle through his kavod or glory?